Heading Disorientation after Right Posteromedial Infarction - Ritsuo Hashimoto; Noriyo Komori; Masako Abe (Case Reports in Neurological Medicine)
We report the case of heading disorientation following ischemic stroke involving the right posteromedial areas. The patient was administered a new test named the Card Placing Test during which a subject was required to recreate an array of three cards, each of which was randomly placed on eight grids around the subject, before and after the subject’s rotation. Qualitative analysis of his performance after rotation revealed that over half of the errors comprised transposition and rotational offset. His score on the Card Placing Test was compared with those of normal controls (n=11). The results showed that his score on Card Placing Test after rotation was significantly lower than those of controls, whereas there was no significant difference between the case and controls in profile of error types. We infer that the heading disorientation observed in the present case was a result of a derangement of a short-term buffer that integrated information on spatial locations of objects with changes in body directions.